Estimation of Evapotranspiration and Water Budget Components Using Concurrent Soil Moisture and Water Table Monitoring. (24th April 2012) - Rahgozar, Mandana; Shah, Nirjhar; Ross, Mark
Abstract : Simultaneous measurements of soil moisture profiles and water table heads, along a flow path, were used to determine evapotranspiration (ET) along with other components of the water budget. The study was conducted at a small-scale ( 0.8 Km 2 ) hydrologic monitoring field site in Hillsborough County, Florida, from January 2002 to June 2004. Frequency Domain Reflectometry soil moisture probes, installed in close proximity to water table monitoring wells were used to derive changes in the soil water storage. A one-dimensional transect model was developed; changes in the soil water storage and water table observations served as input to determine all vertical and lateral boundary fluxes along the shallow water table flow plane. Two distinct land cover environments, grassland and an alluvial wetland forest, were investigated in this particular study. The analysis provided temporally variable ET estimates for the two land covers with annual totals averaging 850 mm for grassland, to 1100 mm for the alluvial wetland forest. Quantitative estimates of other components of a water budget, for example, infiltration, interception capture, total rainfall excess, and runoff were also made on a quarterly and annual basis. Novelty of this approach includes ability to resolve ET components and other water budget fluxes that provide useful parameterization and calibration potential for predictive simulation models.